Role of Serotonin in MODS: Deficiency of Serotonin Protects Against Zymosan-Induced Multiple Organ Failure in Mice. Issue 3 (March 2015) - Zhang, Jingyao; Pang, Qing; Song, Sidong; Zhang, Ruiyao; Liu, Sushun; Huang, Zichao; Wu, Qifei; Liu, Yang; Liu, Chang
Abstract : ABSTRACT: Zymosan-induced multiple organ dysfunction syndrome (MODS) is a multifactorial pathology that involves the deterioration of function of several organs. 5-Hydroxytryptamine (5-HT) is a small monoamine molecule that is primarily known for its role as a neurotransmitter. Previous studies have shown that 5-HT could serve as an important inflammatory mediator in the peripheral immune system. In the present study, we investigated the effect of 5-HT on the development of non–septic shock caused by zymosan in mice. Tryptophan hydroxylase 1–knockout mice ( TPH1 −/−, leading to the absence of 5-HT), TPH1 −/− + 5-hydroxytryptophan (precursor of 5-HT) treatment mice, wild-type ( TPH1 +/+ ) mice, and wild-type plus p -chlorophenylalanine (PCPA, TPH1 inhibitor) treatment mice received zymosan intraperitoneally at a dose of 500 mg/kg. Organ failure and systemic inflammation in the mice were assessed 18 h after the administration of zymosan. Deficiency of 5-HT caused a significant reduction of the 1) peritoneal exudate formation, 2) neutrophil infiltration, 3) MODS, 4) nitrosative stress, and 5) cytokine formation. In addition, at the end of the observation period (7 days), deficiency of 5-HT in the mice was shown to be able to alleviate the severe illness characterized as systemic toxicity, significant loss of body weight, and high mortality caused by zymosan. In conclusion, the lack of 5-HT by genetic knockout or by pharmacologic inhibition of the TPH1 enzyme significantly attenuated zymosan-induced MODS.